Studi Penggalian Pengalaman Guru di SMA Negeri 4 Madiun dalam Pembelajaran Daring di Masa Covid-19 - Giovani Hasna Indriani; Diah Priharsari; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The COVID-19 pandemic has changed the face-to-face learning process to online learning. Online learning is one of the learning methods to solve current problems. With the implementation of online learning from home, teachers are required to change the original face-to-face learning plan to rely on a process without face-to-face. The problem with the many complaints at SMA Negeri 4 Madiun can come from confusing technological features, or it can come from individual teachers, or from organizations. The purpose of this study was to explore the experiences of teachers while teaching at SMA Negeri 4 Madiun, such as exploring the learning process, the feelings of teachers when teaching online, the problems faced during the learning process. The data was collected using structured interview techniques, and the qualitative data was analyzed using thematic coding. The results showed that: (1) online learning at SMA Negeri 4 Madiun has been going well, students and teachers can use technology and learning media; (2) a pleasant experience, namely more flexible learning, gaining new knowledge, and disciplined students; (3) unpleasant experiences, namely lack of interaction between teachers and students, students not participating in learning and many obstacles during the learning process; (4) students with network constraints can use school facilities and students who do not participate in online learning have a home visit / call from parents; (5) Online learning is combined with face-to-face learning, giving consultation hours, replacing homework with quizzes.